Peningkatan Konsentrasi Testosteron pada Tikus Akibat Paparan Ekstrak Air Biji Pinang - Akmal, Muslim; Mahdi, Chanif; -, Aulanni’am (Jurnal Veteriner; Vol 11 No 4 (2010), 2010)
Areca catechu which is known in Indonesia as pinang, contains alkaloids such as arecoline, arecaine,arecaidine, arecolidine, guvacine, guvacoline, and isoguvasine. Arecoline has an ability to change gonadmorfofunction, including shape abnormality of sperm. The aim of this research was to find out the prospectof extract betel nut of A.catechu as male anti fertility agents based on its activity to increase the testosteroneconcentration. Animal models used consisted of 5 groups of 2-3 months male rats (Rattus norvegicus,Wistar strain) and induced for 1 week by water extract of betel nut at the dose of 0, 1, 2, 3, and 4 gram/200gram body weight. Testosterone concentration was determined by ELISA technique. The result showedthat extract betel nut of A. catechu is potential source of natural and beneficial male anti fertility agentsas it can increase the testosterone concentration.
Keywords: Male anti fertility, Areca catechu, testosterone, Rattus norvegicus